FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN TEMPAT PENOLONG PERSALINAN - Fransiska, Precelia (JOURNAL OF HEALTH SCIENCE, 2021)
Effort to reduce the risk of MMR, among others, suggest to the community that safe childbirth is assisted by trained health workers and performed in health facilities, midwives are heslth workers, one of which provides health services to mothers and children, and early detection of referral in rural areas.One means of health care for mothers and child is BPM ( Midwife, of Independent Practice). To analyze the factors that influence the decision of pregnant women in choosing the place of labor. The re research was conducted by analytical survey and cross sectional approach, conducted in April-Juli 2021. The sample size is 46 respondents, the technique used is accidental sampling. The data collected uses primary data with questionnaires. Chi-square test is used to analyze data. The results of data analysis showed that the factors of distance,get a p-value of 0.002, education gets a p-value of 0.005 and work gets a p-value of 0.003. The results show that there is an influence with the choice of place for delivery assistance. Keywords : Distance, Education, Occupation and Choice of Place of Birth